Sintesis dan Karakterisasi Dye Sensitized Solar Cells (DSSC) dengan Sensitizer Antosianin dari Bunga Rosella: Rafika Andari - Rafika Andari Rafika Andari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2017)
This research aims were to make and characterize DSSC using anthocyanin sensitizer from rosella (hibiscus sabdariffa) petals, to know the effect of electrolyte concentration and soaking time in dye extract on solar cell's efficiency, and to know the amount of electrical current produced by DSSC from direct sunlight and 150 watt halogen lamp. This research included the production of TiO2 paste, dye solution preparation from rosella petals, electrolyte solution preparation, counter-electrode carbon preparation, DSSC fabrication, testing, and characterization. Research results showed that DSSC could be made by combining inorganic matter such as TiO2 and organic dye from rosella flower extract. The highest efficiency was produced by 30 minutes soaking time. In direct sunlight, the highest efficiency (0,52%) was produced from the electrolyte concentration of 0,5M. Meanwhile, in 150 watt halogen lamp, the highest efficiency (0,49%) was produced from the electrolyte concentration of 0,3M. The DSSC was able to convert solar energy to electrical energy from sunlight and 150 watt halogen lamp with the maximum electrical current of 0,28 mA and 0,09 mA respectively. Therefore, it could be concluded that the main characteristics that determine solar cells performance were structure, type of dye (light absorbance characteristic), electrolyte solution concentration, and the source of light.